Mechanical aspiration thrombectomy for the treatment of pulmonary embolism: A systematic review and meta-analysis. (December 2022) - Chandra, Vishnu M; Khaja, Minhaj S; Kryger, Marc C; Sista, Akhilesh K; Wilkins, Luke R; Angle, John F; Sharma, Aditya M
Introduction: There are no randomized trials studying the outcomes of mechanical aspiration thrombectomy (MAT) for management of pulmonary embolism (PE). Methods: We performed a systematic review and meta-analysis of existing literature to evaluate the safety and efficacy of MAT in the setting of PE. Inclusion criteria were as follows: studies reporting more than five patients, study involved MAT, and reported clinical outcomes and pulmonary artery pressures. Studies were excluded if they failed to separate thrombectomy data from catheter-directed thrombolysis data. Databases searched include PubMed, EMBASE, Web of Science until April, 2021. Results: Fourteen case series were identified, consisting of 516 total patients (mean age 58.4 ± 13.6 years). Three studies had only high-risk PE, two studies had only intermediate-risk PE, and the remaining nine studies had a combination of both high-risk and intermediate-risk PE. Six studies used the Inari FlowTriever device, five studies used the Indigo Aspiration system, and the remaining three studies used the Rotarex or Aspirex suction thrombectomy system. Four total studies employed thrombolytics in a patient-specific manner, with seven receiving local lysis and 17 receiving systemic lysis, and 40 receiving both. A random-effects meta-analyses of proportions of in-hospital mortality, major bleeding, technical success, and clinical success were calculated, which yielded estimate pooled percentages [95% CI] of 3.6% [0.7%, 7.9%], 0.5% [0.0%, 1.8%], 97.1% [94.8%, 98.4%], and 90.7% [85.5%, 94.3%]. Conclusion: There is significant heterogeneity in clinical, physiologic, and angiographic data in the currently available data on MAT. RCTs with consistent parameters and outcomes measures are still needed.